Institutionalizing integrity: rethinking ethical and cultural standards in Kazakhstan's civil service - Khamzina, Zhanna; Buribayev, Yermek; Tileubergenov, Yerazak (Frontiers in Political Science, 2025)
IntroductionEthical conduct in the public sector is crucial for effective governance, yet Kazakhstan's civil service faces persistent ethical deficits and weak regulatory oversight that undermine professional integrity. These shortcomings have eroded discipline and public trust, making them a serious governance concern. This study analyzes the scope of these ethical and regulatory weaknesses and their impact on governance quality.MethodsA multidisciplinary approach was adopted, integrating legal, sociological, and managerial perspectives to evaluate Kazakhstan's civil service ethics. The analysis encompassed a review of formal ethical codes and laws, an assessment of their enforcement mechanisms, and an examination of organizational culture and behavior. This framework provided a holistic view of how ethical norms are institutionalized and practiced within civil service institutions.ResultsThe findings reveal that formal ethical standards exist but are inconsistently enforced due to a lack of robust oversight mechanisms. Ethical principles are poorly integrated into the organizational culture, resulting in frequent lapses in integrity and professionalism. Consequently, unethical practices persist, undermining the efficiency and quality of public service delivery and eroding public trust. Notably, the absence of a clear, enforceable ethics system renders even well-intentioned administrative reforms largely ineffective.DiscussionAddressing these ethical and regulatory gaps is imperative for improving governance. The study offers strategic recommendations, including establishing stronger oversight and accountability bodies, embedding ethics training and integrity measures into civil service practice, and modernizing administrative processes to foster a culture of integrity. Implementing such reforms is expected to strengthen professional standards and rebuild public trust in the civil service. These insights have broader relevance, providing lessons for ethical governance reforms in other national contexts.